A Study on English Translation Skills and Modes of Multimodal Network from the Perspective of Teaching Situation. (11th October 2022) - Guan, Xinxin; Xing, Qin; Zhang, Yuwei
Abstract : With the in-depth research and continuous exploration of English translation skill patterns by multimodal networks, the scope of English translation skill analysis has been extended to other aspects besides words, and the traditional single-mode English translation skill analysis has gradually changed into a systematic English translation skill analysis that integrates language, images, music, and other symbols. From the perspective of situational teaching, this paper studies the skills and modes of English translation by multimodal network. The research shows that 30 books are randomly selected from preschool children's books, primary school books, and junior high school books, among which the highest proportion of multimodal books is 82%, 57%, and 54%, respectively, and the proportion of multimodal network books among 120 literature books is 79%. Translators have a full understanding of the translated content in situational teaching, but in the actual process of translation, they will inevitably face the situation of language integration and word order adjustment. If translators have a certain understanding of the corresponding English translation skills, they can lay a good foundation for English translation skills and ensure the accuracy of translation.